An insider study on strengthening public management and accountability in the CB Board of Liquidators (CB-BOL): Towards developing the climate of public accountability and the management framework for preservation of government resources - Hatta, Teresita O. (Animo Repository, 2021)
My study adopted Yin’s case study research design and methods using participant-observation for collecting case study evidence. It demonstrated Boven’s view of public accountability as a virtue and a mechanism when CB Board of Liquidators (CB-BOL) implemented mandated values of the 1987 Philippine Constitution and complementary laws in synergy with prescribed processes. The results and evidences of measures that strengthened CB-BOL operation from June 2013 to 2018 registered in archival records classified as public documents. The fiscal functions performed for the State contributed largely to Central Bank (CB) insolvency. RA 7653 established Bangko Sentral (BSP) as an independent central monetary authority. It required transfer of selected CB assets and liabilities to provide opening equity of Php 10 billion. RA 7653 formed CB-BOL to dispose retained assets and liabilities of CB within 25 years. Full liquidation of retained liabilities abolished CB. Liquidating dividends acquired from banks closed prior to 1993 augmented CB-BOL’s accountability.